Fetal Outcome of Pre-eclamptic Mothers with Hyperuricemia - Hussain, SS; Choudhury, MBK; Akhter, J; Begum, S; Mowsumi, FR; Azad, MKH (Journal of Dhaka National Medical College & Hospital, 2012)
Pre-eclampsia (PE) is considered as a major cause of maternal and fetal morbidity and mortality. When a pre-eclamptic woman develops associated hyperuricemia then fetal outcome may become worse. To observe the fetal outcome of hyperuricemic pre-eclamptic pregnancy in relation to normo-uricemic pre-eclamptic pregnancy in a hospital based comparative and cross-sectional study 62 pre-eclamptic patients were selected purposively. PE was diagnosed by hypertension and proteinuria. PE patients were divided into two groups by there serum uric acid level - Hyperuricemic & Normo-uricemic. Then fetal outcome markers (Stillbirth and low birth weight fetus) of the study groups were observed. In this study significant increased number of low birth weight fetuses was observed in babies born to hyperuricemic pre-eclamptic mothers in comparison with babies born to normo-uricemic pre-eclamptic mothers. According to the observation the estimation of serum uric acid may be considered in management of pre-eclamptic mothers, especially in lowering the rate of poor fetal outcome. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12192 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 41-43